Exploring post-harvest losses and waste in tomato supply chains: Insights from Kaduna State, Nigeria - Zailani, Shamsudeen (2023)
In recent years, academics from various disciplines, such as local and international organisations, have shown an increasing interest in food waste. Concerns over food security and environmental implications have heightened interest in the subject. While food waste happens at every stage of the food supply chain, researchers are yet to identify the primary generators of food waste as the evidence about the causes of food waste remains fragmentary. Reducing food losses and waste is one of the best ways to improve food security in the coming decades. This study aimed to investigate tomato waste along the supply chain in Kaduna state, Nigeria, using the mixed method approach for data collection. The mixed method approach allowed for a more comprehensive analysis of the complex factors contributing to tomato waste, providing valuable insights into the challenges faced by the tomato industry in the region. The research focuses on waste in the tomato supply chain using the "follow the thing" approach developed by Ian Cook.